Leadership Roles of Administrators as Perceived by Faculty Members in Dance College, Haikou University of Economics - Qiuping, Zhang; Phopet, Vinutthaput (Academic Journal of Rajapruk University, 2024)
The objectives of this study were 1) to study the leadership roles of administrators as perceived by faculty members in Dance College at Haikou University of Economics. and 2) to compare the leadership roles of administrators as perceived by faculty members in Dance College at Haikou University of Economics, classified by gender, age, education level and work experience. The sample consisted of 52 faculty members selected by stratified random sampling by majors, and data were collected using a five-point Likert scale questionnaire, achieving an IOC of .67-1.00 and a Cronbach's Alpha of .91. The data were statistically analyzed by using percentage, mean, standard deviation, t-test, and One-way ANOVA and LSD. The research findings: 1) leadership roles of administrators as perceived by faculty members in Dance College, Haikou University of Economics overall and each aspect showed the highest level, ranked from service providing, decision making, executing, managing, organizing, and promoting 2) the comparison of leadership role found no differences when classified by gender and work experience, both in overall and in specific aspects. However, when classified by age, there was no difference overall. However, in the Managing, a statistically significant difference at the .05 level was found between the groups Less than 30 years and 30-35 years. Similarly, when classified by educational level, no overall differences were found. However, statistically significant differences at the .05 level were revealed in Decision Making and Managing, with the Master’s degree group scoring higher than the Bachelor’s degree group in both areas.